Effects of educational technologies on maternal self-efficacy in preventing childhood diarrhea: a clinical trial - Francisca Mayra de Sousa Melo; Brena Shellem Bessa de Oliveira; Rhaiany Kelly Lopes de Oliveira; Jallyne Colares Bezerra; Maria Jocelane Nascimento da Silva; Edmara Chaves Costa; Lorena Pinheiro Barbosa; Emanuella Silva Joventino Melo (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To evaluate the effect of educational interventions on maternal self-efficacy in preventing childhood diarrhea in mothers of children younger than five years old. Methods: Basic randomized clinical trial involving 280 mothers of children under five years old. Results: There was a statistically significant increase in maternal self-efficacy scores after the application of the video (p= 0.026), booklet (p <0.001) and video and booklet (p <0.001). Conclusion: The combined use of video and booklet proved to be more effective in promoting self-efficacy than the isolated use. Thus, the interventions used in this study have been shown to significantly increase maternal self-efficacy in preventing childhood diarrhea and, therefore, can be used by health professionals as effective tools.